2014
DOI: 10.1002/mpr.1420
|View full text |Cite
|
Sign up to set email alerts
|

Developing an African youth psychosocial assessment: an application of item response theory

Abstract: This study aimed to refine a dimensional scale for measuring psychosocial adjustment in African youth using item response theory (IRT). A 60-item scale derived from qualitative data was administered to 667 war-affected adolescents (55% female). Exploratory factor analysis (EFA) determined the dimensionality of items based on goodness-of-fit indices. Items with loadings less than 0.4 were dropped. Confirmatory factor analysis (CFA) was used to confirm the scale's dimensionality found under the EFA. Item discrim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 76 publications
0
26
0
Order By: Relevance
“…Notwithstanding its limitations, our study illustrates the value of pursuing a sequential process of testing and refinement in the process of adapting and contextualizing measures such as the ASI and its constituent scales to the particular culture and conditions of life relevant to each refugee population. In that sense, our approach may serve as a guide to other researchers undertaking similar projects in complex cross‐cultural fields, where achieving accuracy of assessment remains a major challenge (Betancourt, Yang, Bolton, & Normand, ). In pursuit of the dual objective of achieving theoretical and ecological validity of measures, our methodology may assist in developing and testing instruments that are both grounded in a general conceptual model and applied within a specific culture and context.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Notwithstanding its limitations, our study illustrates the value of pursuing a sequential process of testing and refinement in the process of adapting and contextualizing measures such as the ASI and its constituent scales to the particular culture and conditions of life relevant to each refugee population. In that sense, our approach may serve as a guide to other researchers undertaking similar projects in complex cross‐cultural fields, where achieving accuracy of assessment remains a major challenge (Betancourt, Yang, Bolton, & Normand, ). In pursuit of the dual objective of achieving theoretical and ecological validity of measures, our methodology may assist in developing and testing instruments that are both grounded in a general conceptual model and applied within a specific culture and context.…”
Section: Discussionmentioning
confidence: 99%
“…Past studies have focused primarily on trauma and ongoing adversity in explanatory models relating to psychiatric disorders such as PTSD (Porter & Haslam, 2005;Steel et al, 2009). Previously, psychosocial measures used in the refugee field have tended to be generic in their focus (Betancourt et al, 2014;Hollifield et al, 2002;Steel et al, 2009). In our approach, we attempted to reconcile a universal theoretical framework (ADAPT) with the particularities of the context and culture under study.…”
Section: Discussionmentioning
confidence: 99%
“…Power for the study is based on a sample size of 480 young adolescents (160 per group), power of 0.80, and α level of 0.05. The study can detect a significant difference between groups if the change over time in APAI [21,22] scores is 2.67, 2.82, and 2.98 greater in one group for ICCs of 0.001, 0.005, and 0.01, respectively.…”
Section: Sample Size and Powermentioning
confidence: 98%
“…The reduced Acholi Psychosocial Assessment Instrument (APAI) was developed for use with young adolescents living in rural, post-conflict Northern Uganda [21,22]. The Internalizing and Prosocial subscales of the APAI were used to assess mental health outcomes.…”
Section: Adolescent Mental Healthmentioning
confidence: 99%
“…In East Africa specifically, some effort has been made to develop instruments containing local idioms to assess common mental health complaints among various populations including Northern Ugandan youth (Betancourt et al, 2009) and Kenyan community-dwelling adults (Ndetei et al, 2006). Prelimiary research has suggested that these ethnographcially-grounded instruments facilitate accurate identification of common mental health complaints (Betancourt et al, 2014; Ndetei et al, 2006). …”
mentioning
confidence: 99%